Pharmacy and its offshoots - Mohd Shafri, Mohd Affendi (Islamic Arts Museum Malaysia, 2018)
The discipline of pharmacy started off as the study of medical materials. In the Muslim tradition, the first person to have written down a text listing the medicinal uses of plants was the Prophet Sulayman ( ) (Solomon). Ibn Abi Usaybi’ah in his ‘Uyun al-Anba’ 1 relays the Prophetic narration2 that a plant emerged when the Prophet Sulayman () was in his prayer niche, upon which he asked its name and use. As other plants appeared, he made the same inquiry. He then had the edible ones taken to be cultivated, while those with medicinal properties were described in writing. This marks the beginning of pharmacy and the medical writing tradition ....